Characterize on the Heisenberg group with left invariant Lorentzian metric - Turhan, Essin; Körpinar, Talat (Walter de Gruyter GmbH, 2009)
In this paper, we consider the biharmonicity conditions for maps between Riemannian manifolds and we characterize non-geodesic biharmonic curve in Heisenberg group H3 which is endowed with left invariant Lorentzian metric. © 2009 Warsaw University. All rights reserved.
Keywords: Geodesic; Heisenberg group; Lorentz metric